A Randomized Trial to Evaluate the Sustained Efficacy of a Mucus Clearance Device in Ambulatory Patients with Chronic Obstructive Pulmonary Disease - Norman Wolkove; Marc A Baltzan; Hany Kamel; Michael Rotaple (Canadian Respiratory Journal)
OBJECTIVE: To determine whether a mucus clearance device (MCD) (Flutter; Axcan Scandipharm, USA) could consistently improve the bronchodilator response and exercise performance in patients with chronic obstructive pulmonary disease (COPD) when used in an ambulatory setting over a one-week period.